The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s40562-016-0053-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress toward reducing the uncertainty in tropical low cloud feedback and climate sensitivity: a review

Abstract: Equilibrium climate sensitivity (ECS) to doubling of atmospheric CO 2 concentration is a key index for understanding the Earth's climate history and prediction of future climate changes. Tropical low cloud feedback, the predominant factor for uncertainty in modeled ECS, diverges both in sign and magnitude among climate models. Despite its importance, the uncertainty in ECS and low cloud feedback remains a challenge. Recently, researches based on observations and climate models have demonstrated a possibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…As reviewed by Kamae et al (2016) and Klein et al (2017), near-surface temperature advection is recognized as an important cloud controlling factor that represents how strongly large-scale atmospheric circulation enhances upward SHF in favor of the formation of lowlevel clouds. As shown in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed by Kamae et al (2016) and Klein et al (2017), near-surface temperature advection is recognized as an important cloud controlling factor that represents how strongly large-scale atmospheric circulation enhances upward SHF in favor of the formation of lowlevel clouds. As shown in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In the ascending branch of the tropical hydrological cycle some observational studies concluded on weak positive correlations between both upper-tropospheric cloudiness and SST, as well as precipitation efficiency and SST (e.g., Lin et al 2006;Su et al 2008), while others observed a narrowing and strengthening of the Hadley cell with smaller average cloud cover (Su et al 2017). Low liquid water clouds in subsidence regions are another key uncertainty for climate sensitivity prediction (Bony et al 2004;Bony and Dufresne 2005;Zhai et al 2015;Kamae et al 2016;Ceppi et al 2017;Klein et al 2017). This study quantifies the cloud cover evolution with SST under both strong ascent and strong descent in instantaneous observations.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the instantaneous radiative forcing and the stratospheric adjustment are spatially uniform, the tropospheric adjustment associated with clouds is likely the key to this mechanism (Fig. 9b; Andrews et al 2012;Sherwood et al 2015;Kamae et al 2015). The horizontal distribution of all-sky and cloud-sky ERFs and the corresponding change in cloud cover (not mediated by the surface temperature change) are illustrated in Fig.…”
Section: B Reinterpretation Of Existing Mechanismsmentioning
confidence: 99%
“…This happens within several days after the initial perturbation but remains as long as the radiative forcing exists (Dong et al 2009;Doutriaux-Boucher et al 2009). At longer time scales, land clouds may decrease with the drying of land associated with the global-mean SAT increase (Fasullo 2010;J08;Joshi et al 2013;Kamae et al 2016), thus enhancing land warming by reducing shortwave reflection.…”
Section: Introductionmentioning
confidence: 99%